Предмет: Алгебра,
автор: Spirius
упростите выражение
Приложения:
Ответы
Автор ответа:
0
Решение на фото
Приложения:
Автор ответа:
0
(1/(b-1)-1(b^2-b))*b/(b+2)-2b/(b^2-4)
1) 1/(b-1)-1(b^2-b)=(b-1)/b(b-1)=1/b
2) 1/b * b/(b+2) = 1/(b+2)
3) 1/(b+2) - 2b/(b^2-4)= 1/(b+2) - 2b/(b-2)(b+2)= b-2-2b/(b-2)(b+2)= -2-3b/(b^2-4)
1) 1/(b-1)-1(b^2-b)=(b-1)/b(b-1)=1/b
2) 1/b * b/(b+2) = 1/(b+2)
3) 1/(b+2) - 2b/(b^2-4)= 1/(b+2) - 2b/(b-2)(b+2)= b-2-2b/(b-2)(b+2)= -2-3b/(b^2-4)
Приложения:
Похожие вопросы
Предмет: Химия,
автор: nenejjejejsjej
Предмет: Литература,
автор: jubljudova68p63rop
Предмет: Русский язык,
автор: gimazetdinovar25
Предмет: Математика,
автор: леба